The Transformation of Labor's Digital Consumption in a Capitalist Regime YouTube Leslar Entertainment: A Christian Funchs Perspective - Ali Imron Hamid (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research explores the impact that the transformation of social media has had on human communication culture, especially through interactions between celebrities and fans in vlog content on Leslar Entertainment's YouTube channel. The focus is not only on changing digital consumption patterns, but also on the role of social media in the context of capitalism. Using social theories, such as the concepts of presumption, playboard, and digital labour, this study underscores the changes taking place in modern society driven by the logic of power accumulation and accelerated accumulation. The concept of time in labour value theory is also used to identify social media as a reflection of the changing regime of time in modern society. Theoretical and interpretive analysis methods were used in researching vlog content and interactions between celebrities and fans on Leslar Entertainment's YouTube platform. The results show that social media, particularly in the context of Lesla's YouTube.